2019
DOI: 10.5039/agraria.v14i4a5677
|View full text |Cite
|
Sign up to set email alerts
|

Gene effects from Bipolaris maydis incidence and severity on popcorn

Abstract: Popcorn suffers severe economic losses resulting from harmful effects caused by several diseases such as southern corn leaf blight (SCLB), which is one of the main leaf diseases able to cause considerable damages to corn crops. The realization conducting genetic studies in order to identify genotypes presenting genetic resistance to this disease it is essential. Accordingly, the aim of the current study is to estimate gene effects and combining abilities in popcorn, with emphasis on the resistance to Bipolaris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The possibility of obtaining superior hybrids can also be inferred, since there are resistant lines from different genealogies, making it possible to explore heterosis. According to Santos et al (2019), non-additive gene effects are more important for the characteristics related to NCLB resistance; therefore, hybridization is the most suitable option for obtaining productive and resistant genotypes. Similar to the findings observed for resistance to E. turcicum (NCLB), when analyzing the resistance characteristics for B. maydis (SCLB), no significant effect was observed for lines during the summer season.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of obtaining superior hybrids can also be inferred, since there are resistant lines from different genealogies, making it possible to explore heterosis. According to Santos et al (2019), non-additive gene effects are more important for the characteristics related to NCLB resistance; therefore, hybridization is the most suitable option for obtaining productive and resistant genotypes. Similar to the findings observed for resistance to E. turcicum (NCLB), when analyzing the resistance characteristics for B. maydis (SCLB), no significant effect was observed for lines during the summer season.…”
Section: Resultsmentioning
confidence: 99%
“…When selecting a population with SCLB resistance characteristics, it may be improved by the addition of resistance and productivity genes, for later extraction of lines and hybrid production. Santos et al (2019) found the importance of the genetic effects of dominance in the control of the resistance characteristics against B. maydis. This is corroborated by studies performed by Carson, Stuber, and Senior (2004) that observed that resistance to SCLB was most influenced by non-additive effects.…”
Section: Resultsmentioning
confidence: 99%